Prevalence and risk factors for carcinogenic human papillomavirus infections in rural Rakai, Uganda. Issue 4 (2nd April 2008) - Safaeian, M; Kiddugavu, M; Gravitt, P E; Gange, S J; Ssekasanvu, J; Murokora, D; Sklar, M; Serwadda, D; Wawer, M J; Shah, K V; Gray, R
Abstract : Objective: To investigate self-administered vaginal swabs for assessing prevalence and correlates of carcinogenic human papillomavirus (HPV) infection in rural Rakai, Uganda. Methods: 1003 sexually experienced women enrolled in a community cohort provided self-administered vaginal swabs collected at annual, home-based surveys. Carcinogenic HPV prevalence, adjusted odds ratios (AOR), 95% confidence intervals (CI) and associated risk factors were determined. Results: Carcinogenic HPV prevalence was 19.2%: 46.6% among HIV positive and 14.8% among HIV negative women (p<0.001). Type-specific prevalence ranged from 2.0% (HPV 16 and 52) to 0.2% (HPV 31). Age-specific HPV prevalence decreased significantly (p<0.001) among HIV negative women; however, the decrease among HIV positive women was not as pronounced (p = 0.1). Factors independently associated with carcinogenic HPV infection were HIV (AOR 4.82, CI 3.10 to 7.53), age (AOR 4.97, 95% CI 2.19 to 11.26 for 15–19 year olds compared to 40+ years), more than two sex partners in the past year (AOR 2.21, CI 1.10 to 4.43) and self-reported herpes zoster, candidiasis or tuberculosis (AOR 4.52, CI 1.01 to 20.31). Married women were less likely to have prevalent carcinogenic HPV (AOR 0.46, CI 0.30 to 0.70). Conclusions: HPV prevalence and correlates measured using self-administered vaginal swabs were similar to studies that use cervical samples. Thus, self-collection can be used as a substitute for cervical specimens and provide an important tool for research in populations unwilling to undergo pelvic exam.